Atividade de fosfomonohidrolases presentes em fígado de girino de rã-touro (Lithobates catesbeianus) durante a metamorfose - Santana, Caroline Carla [UNESP] (2015)
The liver is an important organ in animal metabolism, being responsible for the processing and distribution of nutrients through the blood system to other organs and tissues. Since the liver is responsible for various processes of synthesis and concerning the lack of information about the functions of liver acid and alkaline phosphatases, the aim of the study was to analyze the activities of these enzymes involved in phosphorus metabolism of bullfrog's tadpoles (L. catesbeianus) during metamorphosis, aiming to a better understanding about this period of life of the animal and to produce healthy juveniles. Metamorphosis is a crucial stage in amphibian's development, it is characterized by a series of events that enable tadpoles to occupy the terrestrial environment. During metamorphosis and terrestrial adult stage, the acid phosphatase present in the liver acts as an indicator of lysosomal activity, it can be observed by the increase in its activity at the end of the metamorphic climax, suggesting increased cell death due to recycling of nutrients. The liver alkaline phosphatase, a membrane bound enzyme, acts as a phosphomonohydrolase and in the detoxification of compounds, especially phosphate esters generated in animal metabolism. The decrease in alkaline phosphatase activity when an artificial substrate is used demonstrates a reduction in the generation of secondary metabolites because there is no food intake at this stage of life, on the other hand the use of a physiological substrate suggests an important role in protecting the organism.